Association between Aggregatibacter actinomy-cetemcomitans bacterial load and NLRP3 inflam-masome activation in periodontitis patients with Diabetes - al-obaidi, Mohammed J.; Al-Ghurabi, Batool H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Aggregatibacter actinomycetemcomitans is one of the most common periodontal pathogen that has a direct effect on periodontium. Diabetes and periodontitis considered as chronic diseases with a bidirectional relationship between them. Evidence has shown that the Node Like Receptor Pyrine-3  inflammasome, is crucial for both illnesses.Objectives: This investigation was conducted to observe the association between bacterial load of A. actinomyctecomtans and serum level of NLRP3 inflammasome in periodontitis patient with and without type 2 DM and control group.Materials and Methods: This case-control study included 85 participants, whose ages ranged from (23-55) years. Split into three groups; the control group, which had a clinically and systemically healthy periodontium, and the two groups with periodontitis, one of which also had type 2 DM. Samples of the four most profound periodontal pockets were sampled for subgingival plaque, and from the gingival sulcus in the control group. The real-time (PCR) was utilized in this experiment. to quantify A. actinomyctecomtans DNA was isolated from samples of dental plaque. All subjects' serum was collected, and the concentration of NLRP3 was measured using an ELISA technique.Results: The results showed that the bacterial count was higher in two groups of patient than the control group, but there were no-significant differences. On the other hand, there was a significant correlation between the bacterial count and periodontal parameters in periodontitis with type 2 DM group, while in periodontitis group there was positive correlation with clinical attachment loss and bleeding on probing. A significant positive correlation also noticed between NLRP3 inflammasome and periodontal parameters in periodontitis patient with type2 DM. Regarding the group of periodontitis patients without systemic disease there was no significance correlation between inflammasome and clinical parameters. Finally, there is a non-significant correlation of A. actinomyctecomtans with inflammasome.Conclusions: A. actinomyctecomtans detection rate was strongly higher in patient groups compared to healthy subjects but statically non-significant. Moreover, the lack of correlation between A. actinomyctecomtans and the NLRP3 inflammasome indicates that NLRP3 activation is associated   with inflammatory processes that are induced by a number of external factors, other than bacteria.